2017
DOI: 10.3892/mmr.2017.8215
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box protein O3 suppresses uveal melanoma development by increasing the expression of Bcl‑2‑like protein 11 and cyclin‑dependent kinase inhibitor 1B

Abstract: Forkhead box protein O3 (FoxO3a) is a forkhead box family transcription factor which serves an important role in a number of biological functions, including tumor growth. A previous study indicated that FoxO3a serves a role in insulin like growth factor‑induced growth, migration and invasion of uveal melanoma (UM) cells; however, whether FoxO3a is associated with the development and formation of UM remains unknown. In the present study, the role of FoxO3a in UM development and formation was investigated by mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In the next step, we investigated the effects of PI3K/Akt and FoxO3a inhibitors on Pristimerin effects on phosphorylation and expression protein level of FoxO3a, a transcriptional factor that regulates gene expression, essential for cell cycle arrest and apoptosis in its dephosphorylated form in a nuclear location 35,36 . Figure 7A‐D indicated that both LY294002 and Akt siRNA treatments strongly potentiated the inhibitory effect of 3 μM Pristimerin on Akt (Ser473) and FoxO3a (Ser253) phosphorylations, when compared to the respective control groups.…”
Section: Resultsmentioning
confidence: 99%
“…In the next step, we investigated the effects of PI3K/Akt and FoxO3a inhibitors on Pristimerin effects on phosphorylation and expression protein level of FoxO3a, a transcriptional factor that regulates gene expression, essential for cell cycle arrest and apoptosis in its dephosphorylated form in a nuclear location 35,36 . Figure 7A‐D indicated that both LY294002 and Akt siRNA treatments strongly potentiated the inhibitory effect of 3 μM Pristimerin on Akt (Ser473) and FoxO3a (Ser253) phosphorylations, when compared to the respective control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Another report also found the pristimerin-induced melanoma cell death via inhibiting PI3K/Akt/FOXO3 signalling pathway [42]. Fengxia Yan also found that FOXO3 suppressed melanoma development by increasing the expression of Bcl2like protein 11 (BCL2L11) and cyclindependent kinase inhibitor 1B (CDKN1B) [43]. By consulting the existing literature, we found that FOXO3 did play an anti-tumor role in UVM.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have reported that FOXO3a is a downstream factor of PI3K/AKT that inhibits the survival, growth, migration and invasion of uveal melanoma cells, as well as inducing cell cycle arrest at G1 phase and apoptosis by transcriptionally regulating the expression of its downstream genes, including Bcl-2-like protein 11, cyclin-dependent kinase inhibitor 1B, survivin and cyclin D1 (21,23,24,36). Furthermore, FOXO3a triple mutant overexpression sensitized melanoma cells to apoptosis induced by temozolomide (22).…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with previous reports. However, in addition to transcriptionally regulated genes related to cell cycle and apoptosis (21,23,24,36), there was an alternative mechanism for FOXO3a in the development of melanoma; it was observed that FOXO3a regulated aerobic glycolysis by regulating the expression of SIRT6, which is recognized as a major regulator of cellular metabolism in cancer (8).…”
Section: Discussionmentioning
confidence: 99%